Characterizing urban heat islands in karst areas-the case of Kunming and Guiyang in Southwest China - Fan, Ruixue; Wu, Yangyang; Chen, Qiwei; Wang, Youjin; Li, Lianjin; Shi, Dongyu; Xu, Rong; Xia, Yuting; Cheng, Yuting (Frontiers in Built Environment, 2024)
Urban heat island (UHI) has posed a threat to sustainable development, and the identification of the spatial characteristics of UHI is a prerequisite for the mitigation of UHI effects. Taking Kunming City and Guiyang City in the karst region of Southwest China as two examples, this study utilized spatial econometric modeling and random forest regression to identify and compare the spatial distribution and impact of urban heat islands related to topographic and urban morphology. The results indicated that the UHI in Kunming and Guiyang mainly monocentrically and polycentrically distributed, respectively, and the urban heat island intensity (UHII) in Kunming was significantly higher than that in Guiyang. The spatial error model effectively reflected the influence of topography and urban form on UHII, and the random forest regression model objectively measured the contribution of different influencing factors to UHII. Enhanced vegetation index (EVI), population density (PD), percentage of impervious surface (PIS), ground sky view factor (GSVF), building density (BD) and percentage of water bodies (PW) had similar effects and contributions to the UHII in the two cities, while urban surface roughness (USR) contributed less than topographic slope (SLOPE) on UHII in Kunming, and the SLOPE contributed less than USR in Guiyang. In the karst ecologically fragile zone, the morphology of Kunming and Guiyang are mainly shaped by the topography, which can be characterized as monocentric and polycentric, respectively. And the UHI distribution and UHII were also closely related to topographic patterns. EVI, SLOPE and PW, all showed inhibitory effects on UHII, and EVI contributed the most. PD, PIS, USR and BD, exacerbate the UHII, with PD contributing the most. The above conclusions can provide a reference for policymakers and urban planners to optimize urban morphology and mitigate urban heat island.